2020
DOI: 10.1016/j.scitotenv.2020.141028
|View full text |Cite
|
Sign up to set email alerts
|

The spread of 2019-nCoV in China was primarily driven by population density. Comment on “Association between short-term exposure to air pollution and COVID-19 infection: Evidence from China” by Zhu et al.

Abstract: Recently, an article published in the journal Science of the Total Environment and authored by Zhu et al. has claimed the “Association between short-term exposure to air pollution and COVID-19 infection” (doi: https://doi.org/10.1016/j.scitotenv.2020.138704 ). This note shows that the stated dependence between the diffusion of the infection and air pollution may be the result of spurious correlation due to the omission of a common factor, namely, population density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 29 publications
1
57
0
2
Order By: Relevance
“…7 Population and/or population density are known to be common factors for the spread of infectious diseases, and, as expected, have been reported as one of the main components in the amplification of the COVID-19 pandemic. 15,16 In this study, we found that positive cases and deaths for COVID-19 had an apparent correlation with altitude; however, these variables were better explained by population density; this trend can be explained by understanding that the larger the population is, the higher the transportation volumes, economic activity, air pollution, social interactions, and virus infections are.…”
mentioning
confidence: 58%
“…7 Population and/or population density are known to be common factors for the spread of infectious diseases, and, as expected, have been reported as one of the main components in the amplification of the COVID-19 pandemic. 15,16 In this study, we found that positive cases and deaths for COVID-19 had an apparent correlation with altitude; however, these variables were better explained by population density; this trend can be explained by understanding that the larger the population is, the higher the transportation volumes, economic activity, air pollution, social interactions, and virus infections are.…”
mentioning
confidence: 58%
“…In addition, this is validated by the second sensitivity analysis, where the removal of Los Angeles, i.e., highly polluted, has resulted in a positive association between particulates and corona cases. Chan et al (2020) have observed a positive association between short term exposure to particulates and corona incidences in China, which is contested to be spurious by Copiello and Grillenzoni (2020) . With a systematic review of the literature, Copat et al (2020) point out that PM 2.5 is closely associated with COVID-19 than PM 10 due to the inability of the latter to penetrate type II alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 120 cities in China showed that a 10 μg/m 3 increase in PM of <2.5 μm in aerodynamic diameter (PM 2.5 ) led to more than a 2% increase in new COVID-19 cases ( Zhu et al, 2020b ). However, it was argued that this rise in COVID-19 infection was related to the high population density rather than the short-term exposure to air pollution ( Copiello and Grillenzoni, 2020 ). PM 10 and PM 2.5 were found to be associated with the COVID-19 incidence in Xiaogan, China ( Li et al, 2020 ).…”
Section: Pm and Covid-19mentioning
confidence: 99%